1999
DOI: 10.1093/geronb/54b.1.s24
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects and Health Appraisal: A Meta-Analysis

Abstract: Objective. The purpose was to clarify the effects of methodological variables in the research on age differences in self-rated health and specifically the effects of: (a) the item type used to solicit the appraisal, (b) the approach to sampling, and (c) the criteria for assembling the age groups for study.Methods. Studies differing on these dimensions were compared using meta-analytic techniques. Seventeen usable samples were grouped according to the age comparisons-seven compared "young" and "old" samples whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 33 publications
4
39
3
Order By: Relevance
“…6165 Also as expected, older adults had worst SRH than did younger adults. 66,67 As with SRH, SES and physical activity had a positive effect on mental health. In line with previous work, older adults had better mental health than did younger adults.…”
Section: Discussionmentioning
confidence: 96%
“…6165 Also as expected, older adults had worst SRH than did younger adults. 66,67 As with SRH, SES and physical activity had a positive effect on mental health. In line with previous work, older adults had better mental health than did younger adults.…”
Section: Discussionmentioning
confidence: 96%
“…This notion is supported by researchers who suggest that SRH tends to decline with age (Roberts, 1999) as health generally declines. Nevertheless, SRH is largely stable during middle adulthood (between 20 and 50 years) where adults report generally high levels of SRH (McCullough & Laurenceau, 2004), and the female sex seems to be especially protective against SRH decline (Verropoulou, 2012).…”
mentioning
confidence: 78%
“…Where global SRH and comparative SRH have been used in the same study global SRH was found to be a better predictor of mortality than an age-referential comparative SRH (Vuorisalmi et al 2005). A meta analysis suggests that comparative SRH shows higher optimism among those aged 75 or over than those aged 65-74 but when global SRH is used the trend is reversed (Roberts 1999), suggesting that both should be included in future studies of the older population. Further studies like those of Jylhä (1994) and Manderbacka (1998) using cognitive interviewing techniques (Willis 2005) are needed to explain further what survey respondents understand by questions and mean by their answers when responding to questions about SRH.…”
Section: Discussionmentioning
confidence: 99%